PENGARUH EFEKTIVITAS PENGENDALIAN INTERNAL, KESESUAIAN KOMPENSASI DAN PERILAKU TIDAK ETIS PADA KENCENDERUNGAN KECURANGAN AKUNTANSI - Regina, Dewa Ayu Inmas; Ramantha, I Wayan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.09.TAHUN.2024, 2024)
The purpose of this study is to examine the effectiveness of internal control, the appropriateness of compensation and unethical behavior of the accounting fraud tendency in LPD Gianyar Regency. The method of sample determination which is used is probability sampling technique with proportionate stratified random sampling method using the Slovin formula. The sample in this study amounted to 219 respondents from 73 LPD in the LPD Gianyar regency. Technical analysis of the research using multiple linear regression analysis. Based on the results of this study, it is known that the effectiveness of internal controls and the suitability of compensation have a negative effect on the tendency of accounting fraud. Meanwhile, unethical behavior have a positive effect on the accounting fraud. The result of this study are in line with the agency theory and fraud triangle theory.